Surgical traction of retained maxillary canine associated with the presence of an odontoma, radiographic diagnosis. Case report - Ullaguari-Landeta, María (2021)
The odontoma is a mixed benign tumor of odontogenic origin although its behavior corresponds to a hamartoma, which is composed of differentiated mesenchymal and epithelial cells, making it a normal appearance but with a defective structure. This type of lesions are discovered with the routine radiographic examination, the most common reason for consultation is the lack of eruption of a permanent tooth, with or without the persistence of the temporal tooth. In this article we present a surgical-orthodontic case of an impacted upper canine in a pediatric patient, accompanied by the extraction of an odontoma, with a complete clinical and radiographic diagnosis (tomography). We present the case of a pediatric patient of 12 years of age with dental retention of the right upper canine, caused by the presence of a compound odontoma. Various radiographic studies are carried out for its diagnosis, consisting of panoramic radiography and intraoral radiographs. Surgical orthodontic joint treatment is performed.